Tectonic Fracture Characterization and Stress Analysis in Complex Fault Block Formations: A Case Study in the Second Member of Dengying Formation in Central Sichuan - Yu Fan; Jianhua Guo; Xu Yang; Xihui Hu; Xinyu Shen; Qiutong Wang; Yijia Tang (Geofluids)
The Dengying Formation within Pengtan 1 well area in the Sichuan Basin is a vital gas reservoir for exploration and development. The reservoir is situated in a complex fault block structure characterized by multistage fault evolution, leading to a complicated distribution of tectonic fractures crucial for the accumulation and migration of oil and gas. This study establishes a geological model to describe the fault patterns observed in the region and conducts numerical simulations of the paleotectonic stress field. Moreover, we combine rock fracture criteria and strain and surface energy theories to predict tectonic fractures quantitatively. Our findings indicate that the tectonic fractures in the study area predominantly consist of shear fractures, with primary development of low-angle and oblique fractures and, to a lesser extent, high-angle fractures. These fractures generally exhibit trends in the north–northwest (NNW), northeast (NE), nearly east–west (EW), and nearly south–north (SN) directions. Most fractures formed during the Yanshanian–Himalayan period are identified as effective fractures. The maximum and minimum principal stress values recorded for the Himalayan period of tectonic activity were 150–180 and 120–150 MPa, respectively. Faults significantly influence the distribution of tectonic stress, and stress concentration usually occurs near the fault. A significant correlation exists between tectonic stress and burial depth, exhibiting lower stress levels at shallower depths. In addition, the linear density of fractures gradually decreases from the fault core to its periphery and further decreases to areas far away from the fault. In these three regions, fractures mainly develop in the order of high angle, oblique, and low angle. This study enhances our understanding of the fracture dynamics within the Dengying Formation, contributing valuable insights into the region’s geomechanical properties and potential hydrocarbon exploitation strategies.